Portrait of Sir James Clarke Ross, 1800-1892 - Unknown (University of Southern California Digital Library (USC.DL), 2012)
Portrait of Sir James Clarke Ross, 1800-1892, an illustration from a water color by an unknown artist, in the Royal Geographical Society. Taken from the plate opposite p. 40 titled "Sir James Clark Ross" in book: British polar explorers.; Sir James Clark Ross was a famous British Arctic and Antarctic explorer. The Ross Sea and Ross Ice Shelf in Antarctica are named for him.